A National Population-Based E-cohort of People with Psychosis (PsyCymru) Linkage of Phenotypical and Genetic Data to Routinely Collected Records. (2018) - Lloyd, Keith; John, Ann; Craddock, Nick; Walters, James; Linden, David; Jones, Ian; Bentall, Richard; Lyons, Ronan; Lee, Sze Chim; Owen, Michael
No abstract available